An Expeditious Enantiospecific Total Synthesis of (–)-Crassalactone C - Prasad, Kavirayani R.; Kumar, S. Mothish (Synthesis, 2013)
A concise and expeditious approach for the total synthesis of bioactive styryllactone (–)-crassalactone C is presented from tartaric acid. The main features of the synthesis include the desymmetrization of dimethylamide of tartaric acid and the effective use of cinnamoyl ester as a protecting group as well as a reactant in the ring-closing metathesis reaction.
Keywords: crassalactone C; natural products; stereoselective synthesis; styryllactone